Addressing high vaccination coverage in primary health care settings: challenges and best practices - Bobby Paul; Indranil Saha (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
It is an undoubted fact that vaccines have proven to be one of the most successful public health interventions to combat the burden of infectious diseases in a cost effective manner thereby alleviating adverse health consequences and improving quality of life in the population. Vaccines can save countless lives in a country provided there is an ongoing successful immunization programme with high vaccine uptake rates. This in turn depends on many factors such as population understanding of the need and value of vaccination, availability of vaccines and accessible immunization services through all levels of health care, especially primary health care services.